2008
DOI: 10.1136/oem.2008.039222
|View full text |Cite
|
Sign up to set email alerts
|

Incident and recurrent back injuries among union carpenters

Abstract: Carpenters with long periods of work disability following back injury warrant accommodation and perhaps better rehabilitation efforts to avoid re-injury. Challenges to workplace accommodation and limited ability to clearly define readiness to return to work following injury demonstrate the need for primary prevention of back injuries through attention to engineering solutions among carpenters involved in strenuous work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 41 publications
2
49
1
Order By: Relevance
“…This is not surprising since biomechanical studies have demonstrated how low backloads during common patient handling tasks frequently exceed recommended safe limits for maximal acceptable compressive forces on the back (10,11). The problem is further aggravated because, when first initiated, a history of back pain or injury is associated with recurrent back injury (12)(13)(14), which is often more severe and costly than the initial episode (12,14).…”
mentioning
confidence: 92%
“…This is not surprising since biomechanical studies have demonstrated how low backloads during common patient handling tasks frequently exceed recommended safe limits for maximal acceptable compressive forces on the back (10,11). The problem is further aggravated because, when first initiated, a history of back pain or injury is associated with recurrent back injury (12)(13)(14), which is often more severe and costly than the initial episode (12,14).…”
mentioning
confidence: 92%
“…3 Workers with back re-injuries or pain recurrences have higher costs and durations of disability, 4 yet occupational back re-injuries are rarely studied relative to initial injuries. 5 No generally agreed upon case definition of occupational back re-injury exists, challenging further research efforts in this field. Additionally, re-injuries are not distinguished among general occupational injuries by the US Bureau of Labor Statistics; national re-injury statistics are unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, re-injuries are not distinguished among general occupational injuries by the US Bureau of Labor Statistics; national re-injury statistics are unavailable. 5 Reported prevalence estimates range from 5-82%; 6 this wide range likely reflects the variation and inconsistency regarding definitions and data sources. In addition, few predictors of re-injury have been assessed across multiple studies and even when the same variable has been assessed in multiple studies, there have been conflicting findings.…”
Section: Introductionmentioning
confidence: 99%
“…While secondary prevention may be warranted, among these workers we have been unable to identify factors that are strongly associated with recurrent back injuries other than prolonged work disability with the initial injury [Lipscomb et al, 2008b]. With only 5% of these injured carpenters experiencing a month or more of time away from work with their first injury, targeted secondary prevention that will have substantive impact on costs among this population is difficult to operationalize.…”
Section: Discussionmentioning
confidence: 82%